PENAMBAHAN CLIENT DAN INSTALLASI PRINTER PADA JARINGAN WIFI DI BALAI WILAYAH SUNGAI SUMATERA VII KOTA BENGKULU - mawarni, shindy; Afredo Fadlikal Ilham Aditama; Muhammad Fajhry Amir; Wahyu Redo Ilahi; Sastya Hendri Wibowo (Gayaku Publisher, 2024)
The Sumatra River Basin Office of Bengkulu City functions to have the task of implementing water resources management in river areas which include program preparation, construction implementation, operation and maintenance in the context of conservation and utilization of water resources and control of water damage in rivers, beaches, dams, lakes, lakes and other functions. The computer network at the Sumatra River Basin Office of Bengkulu City currently uses data transmission media on the network in the form of cables and wifi. The data transmission media on the network that is most widely used in daily work is the wifi network. The wifi network provides ease of use and tidiness in the room because it no longer uses cables. The convenience obtained by using wifi includes easy client additions, namely by connecting devices to the network via the specified SSID. In addition to the above, printers connected to the network can help employees in their daily work such as ease of printing reports another needs in work.